In silico docking of phage-displayed peptides targeting Plasmodium vivax apical membrane antigen 1 (PvAMA1) - Chew, C.H.; Lim, Y.A.L.; Chua, K.H. (2018)
Purpose: Plasmodium is an obligate intracellular parasite that rely on the ability in host cell penetration and replication. Apical membrane antigen 1 (AMA1) is one of the most well characterized malarial surface antigen for parasite-host cell invasion and served as a pivotal vaccine candidate and potent antimalarial drug target. The present study aimed to predict the binding sites of three previously selected phage-displayed dodecapeptides, i.e., PdVI (DLTFTVNPLSKA), PdV2 (WHWSWWNPNQLT), and PdV3 (TSVSYTNNRHNL) with affinity to refolded recombinant P. vivax AMA1 (rPvAMA l).